Application Gas, Implementation ICS, and CAF on QFR With HRC Moderating Variable - SUKMA, Aan; HIDAYAH, Nurul (Journal of Governance, Taxation and Auditing, 2023)
This study aims to determine the effect of the application of Government Accounting Standards, the application of Internal Control Systems and Completion of audit findings on the Quality of Financial Statements with Competence of Human Resources as a moderating variable. The research design method uses a survey method with data collection methods using a questionnaire. The population in this study were employees of 32 financial administration employees in the Regional Work Unit (SKPD) of Lahat Regency, using a purposive sampling technique, so that 90 employees were selected as the research sample. The analysis technique used is SmartPLS software version 4.0.8.5. The results of the analysis show that simultaneous and partial testing, the application of Government Accounting Standards, the application of the Internal Control System and the completion of audit findings have a significant effect on the quality of financial reports. Meanwhile, the competence of human resources is not able to moderate the influence between the application of Government Accounting Standards, Internal Control Systems and completion of audit findings on the Quality of Financial Statements. The coefficient of determination is 92.5 percent, while the remaining 7.5 percent is explained by other variables.